КҮНДЕЛИКЛИ БАСПАСӨЗ ТИЛИНДЕ ШАХСТЫ АҢЛАТЫЎШЫ ПЕРИФРАЗАЛАРДЫҢ ҚОЛЛАНЫЛЫЎЫ - Пирниязова, А.К.; Каллибекова, Г.П. (SCIENCE and SOCIETY, 2024)
The article is devoted to the analysis of one of the figurative and expressive means - periphrases. A classification of periphrases used in newspaper texts has been made.